PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR PADA PERUSAHAAN BERKAPITALISASI BESAR (BIG CAPITALIZATION) - Susilo Stevy (Business Accounting Review, 2015)
Research to identify the affect of Corporate Social Responsibility (CSR)  to investor response had been done many times, but the results were inconsitent. The objective of this research was to identify the affect of CSR to investor response in big capitalization company. CSR was measured by Global Reporting Initiative (GRI) Index and investor response that was measured by Cumulative Abnormal Return (CAR). Meanwhile this study used Return On Asset (ROA), firm size, Debt to Equity Ratio (DER), dan market share as control variables. This research was done in big capitalization company group (Big Cap) in factbook issued by Indonesia Stock Exchange in the period of 2008-2012. This research used 238 firm years sample and tested by SPSS 20.The results of this research conclude that CSR has significant positive affect on CAR, which means investor considering CSR to make investment decision. While DER and market share had no siginificant effect on CAR. ROA and firm size had significant negative effect on CAR.